Virulence characterization of Rift Valley fever virus strains and efficacy of glycoprotein subunit vaccines in mice - Balogh, Aaron Michael (Kansas State University, 2017)
Rift Valley fever virus (RVFV) is a vector-borne zoonotic pathogen endemic to sub-Saharan Africa and the Arabian Peninsula that causes severe disease in ruminants and humans. RVFV is a significant threat to US livestock and public health due to a lack of licensed, efficacious vaccines and its ability to become established in non-endemic areas. Subunit vaccine candidates based on RVFV N- and C-terminal glycoproteins (Gn and Gc) are a viable option for use in ruminants due to their ease of production, safety, and ability to induce immune responses that offer differentiation between infected and vaccinated animals (DIVA). Importantly, subunit Gn+Gc vaccine candidates have demonstrated efficacy in sheep. However, despite the efficacy of a dual glycoprotein vaccine, no studies have directly compared protective efficacies of the individual glycoproteins. Furthermore, although RVFV demonstrates 2.1% maximum pairwise amino acid strain divergence within Gn/Gc ectodomains, it remains unclear how this may affect cross-protective vaccine efficacy. In this study, we used a BALB/c mouse model to determine the median lethal dose (LD₅₀) of 3 wildtype RVFV strains and used this information to standardize challenge doses in subsequent vaccine efficacy studies using baculovirus-expressed Gn/Gc antigens derived from RVFV strain Zagazig Hostpital 1977 (ZH548). Strains Kenya 2006 (Ken06) and Saudi Arabia 2001 (SA01) demonstrated equally high virulence (LD₅₀= 7.9pfu), while recombinant strain South Africa 1951 (rSA51) was less virulent (LD₅₀=150pfu). Following prime-boost vaccination, 100% (10/10) of the Gn+Gc vaccinated mice survived challenge with x1000 LD₅₀ Ken06 and SA01, while only 50% (5/10) of Gn+Gc vaccinated mice survived challenge with rSA51. Additionally, 90% (9/10) of Gn-only vaccinated and 40% (4/10) of Gc-only vaccinated mice survived challenge with Ken06. These data suggest that a Gn-only subunit vaccine is an efficacious alternative to dual glycoprotein vaccine candidates and that our ZH548-derived Gn+Gc vaccine has the potential to cross-protect against divergent RVFV strains. Results from this study can be used to optimize current vaccine formulations and inform future vaccine efficacy and licensure studies in ruminants.
Keywords: Rift Vally fever virus; Virology; Vaccine; Virulence; Animal model; Mouse